DESIGN OF WOODWOOD MACHINERY USING ROUTER: DESIGN OF WOODWOOD MACHINERY USING ROUTER - Rusdiyantoro, Rusdiyantoro (Tibuana, 2018)
The art of carving or engraving ornament is the image with certain parts, usually concave, convex or flat, patterned and has a motive. Sculpture can be formed pictures on wood, acrylic, or other materials. In making this product a design researcher perform analysis or potential problems that occur with experiments in doing a good carving designs are done by hand or automatically The definition is a prototype assessment products through on eor more dimensions of concern. In the process of making utensils or equipment requires some work benchesare wont to do in the workshop in general. After the finished product made testing will be conducted experiments in order to know the performance of the products. Testing is carried out using a sample design engraving. The concept of design and manufacture of the products is a bigpart of engineering Activities. This activity starts with he obtained perceptions about human needs, which are then followed by the concept, then designing, developing and refining the product, ending with the manufacture of the product